Earthquake exposure during adolescence and later-life depressive symptoms: A national cross-sectional survey - Yan Liu; Yating Liu; Yantao Wang; Zhuo Li; Yanan Luo (Elsevier, 2023)
Background: This study aimed to examine the association between exposure to the 1976 Great Tangshan Earthquake (GTE) in adolescence and later-life depressive symptoms and to investigate the potential mechanisms underlying this association. Methods: Data were from the 2015 China Health and Retirement Longitudinal Study (CHARLS). The 10-item short form of the Center for Epidemiologic Studies Depression scale (CESD-10) was chosen to measure depressive symptoms. We used the difference-in-difference (DID) method, binary logistic regression models, and multilevel logistic regression models to explore the association of earthquake exposure during adolescence with later-life depressive symptoms. Additionally, multilevel mediation analysis with structural equation modeling (MMSEM) was conducted to investigate potential mechanisms. Results: We identified that adolescent exposure to earthquakes was related to a lower risk of depressive symptoms in later life (OR = 0.90, P = 0.019; OR = 0.48, P = 0.031; OR = 0.47, P = 0.034, respectively). However, this significant association was observed only in females (OR = 0.83, P = 0.028; OR = 0.46, P = 0.053; OR = 0.42, P = 0.037, respectively). Moreover, social activity participation played a mediating role in the association between exposure to earthquakes in adolescence and later-life depressive symptoms. Conclusions: We observed a lower risk of depressive symptoms in later life in survivors of earthquake exposure during adolescence. Further, we found the mediating role of social participation in the association between earthquake exposure in adolescence and later-life depressive symptoms, which gives support for the posttraumatic growth (PTG) theory. Our findings imply that, in order to lower the risk of depression in later life following exposure to a natural disaster in adolescence, it is necessary to take into account the buffering effect of social participation.